(untitled) (Global Journal of Management and Business Research, 2023)
The article was developed using an exploratory research method in conjunction with a bibliographical survey on the issues of Greenhouse Gas -GHG emissions, correlating the emission rate with the rate of change in global temperature, demonstrating that GHG emissions cannot be attributed to cause of global temperature rise. Another subject analyzed is the possible cause of the gradual decrease in deposits of Clean Development Mechanism projects -CDM registered by Brazilian companies in the UNFCCC, presents in the discussion the lack of attention to the subject of the competent public agencies, bringing as a consequence the delay in the regulation of the carbon credit market, thus allowing commercial speculations that are prioritized over environmental actions.